EFFICACY OF TISSUE PLASMINOGEN ACTIVATOR, HEPARIN AND STREPTOKINASE IN PATIENTS WITH SUB MASSIVE PULMONARY EMBOLISM IN A TERTIARY CARE CARDIAC HOSPITAL - Ahmed, Imran; Riaz, Ayesha; Kamran, Javeria; Siddiqui, Abdul Hameed; Yousaf, Hasnain; Abbas, Shujja; Abbas, Kamran; Tuyyab, Farhan; Iqbal, Tahir; Aziz, Sohail (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the clinical characteristics and outcomes of 25 cases of pulmonary embolism in relation to use of thrombolytic and anticoagulants.Study Design: Case series study.Place and Duration of Study: Adult cardiology department of Armed Forces Institute of Cardiology & National Institute of Heart Diseases from Oct 2017 to Jan 2018.Material and Methods: Total 25 patients with pulmonary embolism were included in the study using consecutive sampling technique. Clinical characteristics and outcomes of the patients were noted and analyzed. SPSS-23 was used for data analysis.Results: Twenty five cases of acute pulmonary embolism were included in our study and were admitted to the coronary care unit of hospital during the study period. Mean age of patients was 42 ± 18.32 years with minimum age 20 years and maximum 83 years. There were 19 (76.0%) male patients while 6 (24.0%) female patients. Most common NYHA class with which patients presented was, class-II 10 (40%) followed by class-III 8 (32%). The most common CT pulmonary angiogram finding of the patients was bilateral segmental embolism 17 (68.0%). Out of 25 patients, 12 (48.0%) patients received streptokinase and four (16%) received tissue plasminogen activator. Four patients were found to have deep venous thrombosis. Mortality was 20%.Conclusion: Acute pulmonary embolism is a relatively common medical emergency and accurate diagnosis in early period can help institute appropriate thrombolytic therapy to maximally benefit the patients.